Analyzing Educational Managers' Readiness for Chat GPT Adoption Using a Cross-Relationship Matrix: A Quantitative Investigation - Sadaf Suhail Zaidi; Hammad Ahmad; Faisal Altaf; Sanum Malik (Review Journal of Social Psychology & Social Works, 2024)
Purpose of the Study: The purpose of this research study was to explore the factors influencing the readiness of educational managers for the adoption of Chat GPT in higher education, specifically within the Social Sciences faculties of universities in Lahore, Pakistan.